PENGARUH MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) DISERTAI MEDIA GAMBAR TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMP NEGERI 1 TAMBUSAI UTARA - SUKMANA, EIS (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aim to know thete is effect or not effect of  Direct Instruction with picture media again  result Natural Science students seventh grade junior high school 1 Tambusai Utara in academic years 2014/2015. This type of research i quasi experimental. The sample was take by using Random sampling technique. Type design of research is non randomized control group pretest posttest design. The sample of researc is VIIB as control class and VIIA as experiment class. Data collection techniques in this study is a test instrument in the form of multiple chioce questions. Basad on result of hypothesis testing obtained tcount > ttable (5,14 > 1,67) so can be concluded that there is influence of model Direct Insruction with picture  media against learning result Natural Science Bayologi of the seventh grade junior high school 1 Tambusai Utara  in academik years 2014/2015